2021
DOI: 10.4102/ajcd.v3i1.47
|View full text |Cite
|
Sign up to set email alerts
|

Psychological states of career wellbeing and affective commitment as predictors of dual career agility types

Abstract: Background: There is limited empirical research on the construct of career agility and the relevance of dual career agility types in the technological-driven workplace.Objective: This study aimed to adopt a person-centred approach in assessing the link between dual career agility types and individuals’ psychological states of career wellbeing and affective commitment.Method: The cross-sectional survey involved a sample of (n = 298) managers (71%) and staff (29%) employed in the human resource and financial ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Participants' awareness of the digital-era world of work offered additional insight into the career agility mindset. The positive associations elucidated participants' propensity for epistemic curiosity into the world of work changes, resulting in career agile external career exploration, self-efficacious career goal setting, and intentional and optimistic career navigation of new chance career and development opportunities proffered by technological advancement (Coetzee, 2021a).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Participants' awareness of the digital-era world of work offered additional insight into the career agility mindset. The positive associations elucidated participants' propensity for epistemic curiosity into the world of work changes, resulting in career agile external career exploration, self-efficacious career goal setting, and intentional and optimistic career navigation of new chance career and development opportunities proffered by technological advancement (Coetzee, 2021a).…”
Section: Discussionmentioning
confidence: 98%
“…Anchored in Savickas's (2013) model of psychological career adaptation, career agility denotes a mindset of adaptivity which is the psychological readiness to embrace the complexities and ill-defined occupational and work challenges of the digital-era world of work (Coetzee, 2021a;Hirschi, Herrmann, & Keller, 2015;Savickas, 2013). Career agility (i.e.…”
Section: Career Agility As a Mindset Of Adaptivitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study conducted by Anwar, Suhariadi, & Fajrianthi, (2018) found that career well-being is closely linked to emotional, psychological, and social well-being, as well as relationship wellbeing between family roles. Research on describing career well-being profiles has been previously conducted (Coetzee, 2021;Rautenbach, 2015;Rothmann, 2014;Millán, et al 2013), but the current study focused on career well-being among school counselors based on their educational qualifications.…”
Section: Introductionmentioning
confidence: 99%